Sosialisasi Dan Pendampingan Pemanfaatan Lahan Kosong Untuk Pengembangan Potensi Wisata Dalam Meningkatkan Kesejahteraan Masyarakat Desa Mojogebang Kecamatan Kemlagi Kabupaten Mojokerto - Sugeng Eko Yuli Waluyo; Diky Irmawan; Efina Nur Ayunin; Amanda Dewi Muttho’siyah; Gustyo Dimas Alfatah; M Ariful Muttakin; Muhammad Shobih; Hilda Ezha Mahenda; Lily Setya Devi; Muhammad Fariz Fahrul Mu’minin; Nita Chrisvianti; Desy Anggraini Rahmadanti; Devi Halimatus Sa Diyah; Doni Mahesa; Eka Putra Tri Rahanda; Farida Ainun N; Habib Muhammad Alawy; Nanik Dyah S.W.W; Khotim Khotim; Nurul Fuadi; M Affandi Eka Putra; Nandana Maharai Delirando Rawi; Sela Kurnianti Khasanah; Naufal Ahmad Firmansyah (Universitas Kristen Indonesia Toraja, 2024)
This community service article aims to utilize empty land, including rice fields, to explore and develop tourism potential in an effort to improve community welfare. Through direct outreach to village residents as well as intensive assistance regarding methods and strategies in efforts to make Mojogebang village a tourist village. What is done is starting from mapping to identify places that have potential tourist destinations, analyzing characteristics and problems, describing the development of community-based tourist villages, as well as analyzing supporting element systems. The recommendations we provide are as follows. Because Mojogebang village is mostly a rice field area, the most appropriate thing to implement there is culinary tourism in the rice fields, namely food stalls or restaurants or cafes with a backdrop and view of the green and yellow rice fields.